2009
DOI: 10.4314/ajdas.v7i2.46362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of substance use among rural high school students in Limpopo Province, South Africa

Abstract: This study documents the prevalence rates for use of cigarette, alcohol, methylated spirit, cannabis, mandrax and cannabis together, glue or thinners among rural high school students in Mankweng, Limpopo Province, South Africa. A multistage sampling procedure produced a sample of 1600 students in grades 9 and 11 who completed a self-administered questionnaire. The prevalence rates for previous mouth (recent) use of alcohol, cigarettes, cannabis glue and spirits were 6.4%, 10.5%, 1.4%, 1.2% and 0,8% respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
2
11
2
Order By: Relevance
“…Furthermore, the 2013 report of the Turkish Monitoring Center for Drugs and Drug Addiction (TUBIM), which includes a statistical finding that the regions of Marmara and Aegean have the highest prevalence in marijuanarelated incidents, with a total of 33,500 drug users being reported for Izmir according to data for 2011, seems to confirm this situation (79). Our study found that the consumption of cigarettes, alcohol, energy drinks, and substances is significantly more prevalent among men than among women, which is consistent with other studies in the literature pertaining to the gender role in this matter (3,5,39,66,77,80,81). Additionally, our study found that the trial of substances was similar in men and women (consumption of 1-5 times), but a difference was found in the continued consumption (more than five times).…”
Section: The Prevalence Of Risky Behaviorsupporting
confidence: 82%
“…Furthermore, the 2013 report of the Turkish Monitoring Center for Drugs and Drug Addiction (TUBIM), which includes a statistical finding that the regions of Marmara and Aegean have the highest prevalence in marijuanarelated incidents, with a total of 33,500 drug users being reported for Izmir according to data for 2011, seems to confirm this situation (79). Our study found that the consumption of cigarettes, alcohol, energy drinks, and substances is significantly more prevalent among men than among women, which is consistent with other studies in the literature pertaining to the gender role in this matter (3,5,39,66,77,80,81). Additionally, our study found that the trial of substances was similar in men and women (consumption of 1-5 times), but a difference was found in the continued consumption (more than five times).…”
Section: The Prevalence Of Risky Behaviorsupporting
confidence: 82%
“…We add new information to the literature about how a rural roadside market environment fosters both substance use and risky sexual behaviors for the young men who work there. No prior study has looked at rural markets M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 24 and the opportunities for risky behaviors they present for young men, although several studies have looked at substance use and risky sex in the context of bars and education settings in Africa (Bisika, Konyani, Chamangwana, & Khanyizira, 2008;Fisher, Cook, & Kapiga, 2010;Hahn, Woolf-King, & Muyindike, 2011;Onya & Fisher, 2008). The rural market differred from those settings because it was an environment where young men both worked and engaged in leisure activities.…”
Section: Discussionmentioning
confidence: 93%
“…Globally, the prevalence rates for use of all substances are higher among males than females (Onya & Fisher, 2008;World Health Organization, 2011). Early alcohol use may have lifelong consequences, including increased risk of later substance use disorders (American Psychiatric Association, 2000;Chen, Storr, & Anthony, 2008).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Commercially brewed beverages are not the only alcoholic drinks consumed by the youth. Onya and Flisher (2008) as well as Gugu and Davison, (2017) report consumption of traditionally brewed alcohol by young drinkers.…”
Section: Drink Of Choice/what Youth Drinkmentioning
confidence: 96%
“…The act of alcohol drinking by young people has steadily increased over the years. While males are reported to be most likely to drink alcohol more than females (Onya & Flisher, 2008;Owo, 2013), research has shown that the gender gap in alcohol consumption behaviour, particularly binge drinking, is narrowing (Ramsoomar & Morojele, 2012). According to Schulte, Ramo, and Brown, (2009) the reduction of the gap between the two gender variables in terms of alcohol use can be attributed to an increase in opportunities for women which allow them to perform roles traditionally set aside for men, enabling and encouraging them to drink more.…”
Section: Introductionmentioning
confidence: 99%